A comparative study of the oxidative system in Chironomidae larvae with contrasting feeding strategies. Issue 1 (1st January 2020) - Szczerkowska-Majchrzak, E.; Jarosiewicz, M.
Abstract: The aim of the present work was to compare the oxidative system in the fourth-instar larvae of four species of Diptera belonging to the family Chironomidae: Chironomus riparius, Paratanytarsus sp., Prodiamesa olivacea and Conchapelopia melanops . These species were selected based on their ecological and biological differences and were assessed in relation to their ecological and biological characteristics. The following parameters of oxidative stress were determined: the levels of total antioxidant capacity (TAC) and reduced glutathione; the activity of the antioxidant enzyme catalase (CAT); the level of malondialdehyde (MDA), a product of lipid peroxidation; and glutathione S-transferase (GST) activity. Results demonstrated significant differences among taxa in the specific activity of most investigated parameters. Prodiamesa olivacea showed the greatest antioxidant protection (activity of CAT, level of reduced glutathione (GSH)) and the highest detoxification activities (activity of GST and level of GSH). Predatory C. melanops was shown to be the most promiscuous biomarker for assessing the total antioxidant activity. We demonstrate that the four chironomid taxa, occupying the same ecosystem, share an important antioxidant enzymatic and non-enzymatic pool, but with oxidative stress parameters differing among the four species.